2021
DOI: 10.3390/metabo11050311
|View full text |Cite
|
Sign up to set email alerts
|

High Glucose Shifts the Oxylipin Profiles in the Astrocytes towards Pro-Inflammatory States

Abstract: Hyperglycemia is associated with several complications in the brain, which are also characterized by inflammatory conditions. Astrocytes are responsible for glucose metabolism in the brain and are also important participants of inflammatory responses. Oxylipins are lipid mediators, derived from the metabolism of polyunsaturated fatty acids (PUFAs) and are generally considered to be a link between metabolic and inflammatory processes. High glucose exposure causes astrocyte dysregulation, but its effects on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…The most interesting data are those about how glucose affects the activation of astrocytes, which is seen during brain damage and is thought to be part of the inflammatory response. A number of previous studies have reported the influence of high glucose on glial morphology and reactivity, both in vitro and in vivo [11,14,31,38]. In experiments in vivo, streptozotocin-induced diabetes in mice led to significantly increased activation of microglia and astroglia, the loss of neurons, and cognitive dysfunctions [38].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The most interesting data are those about how glucose affects the activation of astrocytes, which is seen during brain damage and is thought to be part of the inflammatory response. A number of previous studies have reported the influence of high glucose on glial morphology and reactivity, both in vitro and in vivo [11,14,31,38]. In experiments in vivo, streptozotocin-induced diabetes in mice led to significantly increased activation of microglia and astroglia, the loss of neurons, and cognitive dysfunctions [38].…”
Section: Discussionmentioning
confidence: 98%
“…In vitro, high glucose levels (30 mM/L) resulted in changes in the expression of cytoskeleton proteins such as GFAP and vimentin [12]. Additionally, in astrocytes, high glucose levels can also induce the expression of inflammatory cytokines such as tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), interleukin-1 (IL-1) and interleukin-4 (IL-4) [13,14]. These cytokines are signaling molecules that can promote inflammation and contribute to the progression of diabetic cerebral neuropathy.…”
Section: Introductionmentioning
confidence: 99%
“…The metabesity factor HMG20A is increased under mild inflammation induced by obesity and IR, inducing reactive astrocyte hyperplasia, protecting neurons from metabolic stress, and re‐establishing glucose homeostasis 107 . Regulating COX‐mediated oxylipin synthesis in astrocytes as a novel potential target in the treatment of hyperglycemia‐associated brain injury 108 …”
Section: Gut Microbiota‐astrocyte Axis Connects T2dm With Cognitive D...mentioning
confidence: 99%
“…107 Regulating COX-mediated oxylipin synthesis in astrocytes as a novel potential target in the treatment of hyperglycemia-associated brain injury. 108 The Proinflammatory cytokine produced by dysbacteriosis is an important immune signal that directly activates astrocytes. The db/db mice have significantly increased escape latency at 6, 18, and 26 weeks of age, and their senescence-associated cognitive decline is associated with the gut microbiome.…”
Section: Gut Microbiota and Astrocyte Co-regulate Central And Periphe...mentioning
confidence: 99%
See 1 more Smart Citation